The Effect Of Compensation And Work Environment On Job Satisfaction With Performance As An Intervening Variable (Case Study On Population Control Service Officers, Family Planning, Women's Empowerment And Child Protection, Serdang Bedagai Regency) - Hadi Panjaitan; Diana Florenta Butar-Butar (Universitas Dharma Wacana, 2022)
The results show that Based on the results of the analysis of hypothesis 1 it can be seen that the Compensation variable (X1) From the description iit ican be seen that tcount(11,894)> ttable (2.042), as well as the significance value of 0.000> 0.05, it can be concluded that the first ihypothesis is accepted, meaning that the Compensation variable (X1) has an effect in the Job Satisfaction variable (Z). This means that compensation has ia very good influence in measuring employee satisfaction at work. Based on the results of the analysis of hypothesis 1, it can be seen that the work environment variable (X2). From the description it can be seen that tcount (4.919) > ttable (2.042), and the significance value is 0.000 <0.05, it can be concluded that the second hypothesis is accepted, meaning that the Work Environment variable (X2) has an effect on the Job Satisfaction variable (Z). The results of the analysis of hypothesis 1 can be seen that the Compensation variable (X1) From the description it can be seen that tcount (1,397) < ttable i2,042), as well as the significance value of 0.173> 0.05, it can be concluded that the third hypothesis is rejected, meaning ihat the Compensation variable (X1 ) has no effect on the Performance variable (Y). Based on the results of the analysis of hypothesis 1, it can be seen that the Work Environment variable (X2). From this description, it can be seen that tcount (2,690) > ttable (2,042), and the significance value is 0.012 <0.05, so it can be concluded that the fourth hypothesis siaccepted, meaning that the Work Environment variable (X2) has an effect on the Performance variable (Y). it means that in improving the performance of employees in the agency required a work environment that supports employee performance. Based on the results of the analysis of hypothesis 1 can be seen that the variable Job Satisfaction (Z). From the description it can be seen that tcount (1.891) < ttable (2.042), and the significance value is 0.069 <0.05, it can be concluded that the fifth hypothesis is rejected,meaning that the Job Satisfaction variable (Z) has no effect on the Performance variable (Y)